IMPLEMENTASI SISTEM SMARK UMKM DAN LITERASI INVESTASI PADA UMKM DI KOTA BANDUNG - Lestari, Resanti; Putra Pratama, Vidya Ramadhan (Jurnal Abdimas Sang Buana, 2024)
The Community Service Program (PKM) aims to provide training and mentoring to Micro, Small, and Medium Enterprises (MSMEs) in Bandung City on marketing audits using the SMARK System and investment literacy. Of the 10 invited MSMEs, 7 actively participated in the program, which was conducted both online via Zoom and offline at STIE Ekuitas. The activities included training sessions on marketing audit strategies, practical guidance on utilizing the SMARK application to enhance business efficiency, and an introduction to secure and profitable investment instruments. Participants gained increased understanding of the importance of systematic marketing evaluation and sound financial management, including investment planning. As a tangible output, participants received a SMARK manual book and presentation materials related to marketing audit and investment literacy. These resources are expected to help participants implement the acquired knowledge in improving their business performance. The results of the program indicate that the SMARK System and marketing audits are crucial for MSMEs, enabling them to systematically evaluate and refine their marketing strategies. This initiative contributed by equipping MSMEs with tools to conduct independent marketing audits and offering guidance on financial literacy to utilize safe investment options effectively. Such steps are critical for fostering professionalism, informed decision-making, and long-term sustainability for MSMEs amid increasingly competitive markets. The program’s impact underscores the need for continued monitoring and further training to ensure that MSMEs can fully benefit from and sustain the knowledge and skills acquired through this initiative.